2014
DOI: 10.1590/s1677-5538.ibju.2014.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Application of Human Amniotic Membrane in Canine Penile Tunica Albuginea Defect: First Step toward an Innovating New Method for Treatment of Peyronie?s Disease

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purposes: To evaluate the efficacy of human amniotic membrane (AM) grafting in the canine penile tunica albuginea defect; we developed an animal model as the first step toward an innovating new method for the treatment of Peyronie's disease, penile cancers, and congenital deformities of the penis. Material and Methods:From August to September 2011, ten healthy male dogs were selected. A rhomboid incision about 3x2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The search for a suitable TA substitute for penile surgery has led to testing materials such as human amniotic membrane, lingual mucosa, and buccal mucosa. 20 26 27 Salehipour et al . 26 have documented good integration of grafted amniotic membrane with surrounding tissue, successful reepithelization, increased collagen fiber deposition, reduction of elastic fibers in the upper portion of the repaired area, and no dysplasia in canine TA defects; however, the authors described no data on possible immunological reactions and their study is limited by a relatively short follow-up (12 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…The search for a suitable TA substitute for penile surgery has led to testing materials such as human amniotic membrane, lingual mucosa, and buccal mucosa. 20 26 27 Salehipour et al . 26 have documented good integration of grafted amniotic membrane with surrounding tissue, successful reepithelization, increased collagen fiber deposition, reduction of elastic fibers in the upper portion of the repaired area, and no dysplasia in canine TA defects; however, the authors described no data on possible immunological reactions and their study is limited by a relatively short follow-up (12 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve weeks later, histopathologic evaluation of the grafted site showed normal epithelial and collagen healing suggesting this type of graft for future trials in humans. Nonetheless, not before extensive research on a larger cohort of patients, will we be able to confirm the feasibility and safety of this type of graft? 37 …”
Section: Postoperative Considerations: (Surgical Outcomes/patient Rehabilitation)mentioning
confidence: 99%
“…The ability of dHACM to adapt to host tissue characteristics makes it an ideal substitution for the tunica albugenia. In their canine model, Salehipour et al ( 19 ) found that dHACM grafts showed increased distensibility and elasticity post-operatively. This was confirmed by the presence of elastin fibers on histopathologic examination.…”
mentioning
confidence: 99%
“…This was confirmed by the presence of elastin fibers on histopathologic examination. During subsequent stimulation of artificial erections, the dHACM was able to tolerate high intra-cavernosal pressures without leaking or bulging ( 19 ). This characteristic of dHACM may make it the ideal substitution graft for penile reconstructive surgery.…”
mentioning
confidence: 99%